Airway stenting and tracheobronchoplasty improve respiratory symptoms in Mounier-Kuhn syndrome - Odell, David D.; Shah, Archan; Gangadharan, Sidhu P.; Majid, Adnan; Michaud, Gaetane; Herth, Felix; Ernst, Armin (Chest, 2011)
Background - Mounier-Kuhn syndrome (MKS) is a condition characterized by tracheobronchomegaly resulting from the loss or atrophy of musculoelastic fibers within the airway wall. Concomitant tracheobronchomalacia is seen in most patients with MKS, often leading to significant respiratory compromise due to bronchiectasis, increased dead space, and impaired secretion clearance. - Methods - We report a series of 12 patients with MKS and tracheobronchomalacia who were evaluated at our institution for significant respiratory problems. Stent trials were conducted in 10 patients, with seven proceeding to operative tracheobronchoplasty (TBP) and one continuing with long-term stent placement. One patient underwent TBP without prior stent placement. Of the remaining three patients, two had no improvement with trials of stent placement, and a stent could not be placed in the third because of a large tracheal diameter. - Results - Compared with baseline values, clinically significant improvements in health-related quality-of-life measures and pulmonary function testing were seen in patients who underwent central airway stabilization (n = 9). Complications of both stent placement and TBP were generally mild. However, one death was reported in the surgical group secondary to an exacerbation of preexisting interstitial pneumonia. - Conclusions - An aggressive approach that targets central airway stabilization may improve outcomes for patients with MKS. - Trial registry - ClinicalTrials.gov; No.: NCT00550602; URL: www.clinicaltrials.gov
First published online: 16 December 2015
Gesehen am 29.09.2022